2017
DOI: 10.5152/turkpediatriars.2017.5451
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of blood cultures in a pediatric intensive care unit: a three year evaluation

Abstract: Aim: In this study, it was aimed to retrospectively assess the frequency and antibiotic resistance of microorganisms isolated from blood cultures of patients in a pediatric intensive care unit. Material and Methods: The study was conducted on blood culture tests obtained from patients in a pediatric intensive care unit and sent to a microbiology laboratory between 2013 and 2016. The species and antibiotic susceptibilities were assessed in microorganisms isolated from the blood cultures. Results: Overall, 4239 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
3
0
2
Order By: Relevance
“…Similar findings were also reported in Ethiopia of Jimma (2.23%) [14], Addis Ababa (2.23% and 1.82%) [22,23] and Gondar (2.13%) [24]. However, it was lower than the previous reports from Turkey 6.5% [25], India 6% [26], and Gondar 8.9% [16]. The differences with the findings of this study may be attributed to the variation in geographical area, number of samples examined, the extent of time, and method used for sampling.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were also reported in Ethiopia of Jimma (2.23%) [14], Addis Ababa (2.23% and 1.82%) [22,23] and Gondar (2.13%) [24]. However, it was lower than the previous reports from Turkey 6.5% [25], India 6% [26], and Gondar 8.9% [16]. The differences with the findings of this study may be attributed to the variation in geographical area, number of samples examined, the extent of time, and method used for sampling.…”
Section: Discussionsupporting
confidence: 87%
“…El germen más frecuentemente aislado en hemocultivos contaminados fue S. epidermidis, similar a lo reportado en 2017 por Betül Ergül, de una serie de 3 años en una unidad pediátrica en Turquía 15 , donde reportaron un crecimiento del 7,6% de los hemocultivos tomados, con 45% de aislamiento de Staphylococcus coagulasa negativo que usualmente representan contaminación. Es importante a resaltar que el contaminante del hemocultivo en 4 casos fue un Staphylococcus aureus, en suelen ser patógenos y su determinación como germen contaminante requiere el contexto del paciente para detectarlos 16 .…”
Section: Discussionunclassified
“…In a study by Ertürk et al [18] , these rates were found to be 25% and 50%, respectively. In yet another study, 67.9% of enterococci showed HLGR and 67.9% showed HLSR [19] . In the present study, three patients exhibited both gentamicin and streptomycin resistance, but one was not analyzed for aminoglycoside sensitivity.…”
Section: Discussionmentioning
confidence: 83%